Surgical Treatment after Failed Primary Correction of Urogenital Sinus in Female Patients with Virilizing Congenital Adrenal Hyperplasia: Are Good Results Possible? - Sircili, Maria Helena Palma; Bachega, Tania Sartori Sanchez; Madureira, Guiomar; Gomes, Larissa; Mendonca, Berenice Bilharinho; Dénes, Francisco Tibor (Frontiers in Pediatrics, 2016)
Purpose: Genital reconstruction in female patients with virilizing congenital adrenal hyperplasia (CAH) is very challenging. Our aim was to evaluate the techniques employed to treat complications after failure of primary urogenital sinus (UGS) surgery, as well as the result of these reoperations. Patients and Methods: Twenty girls with virilizing CAH who were previously submitted to genitoplasty in our service and elsewhere had recurrent UGS stenosis and vaginal introitus stenosis that required surgical treatment. The main symptoms were recurrent urinary tract infection (UTI) in nine, dyspareunia in six and hematocolpos in three (two associated with sepsis). The anatomical findings were the persistence of UGS with stenosis in 17 patients and vaginal introitus stenosis in three. The mean age at procedure was 15.2 yrs., averaging 13.1 yrs. after the first surgery. The surgical techniques employed were: isolated perineal flap in 17 patients and perineal flap with partial mobilization of UGS in three. The mean follow-up after the procedure was 4.8 years (varying from 1 to 17yrs). Results: Vaginal dilations were performed after surgery in 15 patients. Good functional and anatomical results were obtained in 15 patients, with vaginal introitus amenable to dilators of 3.0 cm in diameter. Five patients with high vaginal insertion had recurrent vaginal stenosis and required a surgical revision. No patients presented menstrual obstruction or UTI after surgery. Eight of the 15 adult patients are sexually active. Conclusion: The reoperation to treat failed primary UGS treatment using Y-V flap and partial mobilization techniques associated to vaginal dilations, promoted good anatomical and functional results with low morbidity in 75% of the patients. □